Rediscovering Enoch?: the antediluvian past from the fifteenth to nineteenth centuries - Hessayon, Ariel; Reed, Annette Yoshiko; Boccaccini, Gabriele (Studia in Veteris Testamenti Pseudepigrapha, 2023)
The books of Enoch are famed for having been “lost” in the Middle Ages but “rediscovered” by modern scholars. But was this really the case? This volume is the first to explore the reception of Enochic texts and traditions between the fifteenth and nineteenth centuries. Bringing specialists in antiquity into conversation with specialists in early modernity, it reveals a much richer story with a more global scope. Contributors show how Enoch and the era before the Flood were newly reimagined, not just by scholars, but also by European artists and adventurers, Kabbalists, Sufis, Mormons, and Ethiopian and Slavonic Christians